The Complete Person: Comparative Perspectives of Ki Ageng Suryomentaram and Muhammad Iqbal - Mukhamad Sarifudin (Islah: Journal of Islamic Literature and History, 2022)
Muhammad Iqbal and Ki Ageng Suryomentaram are critical thinkers who focus on humans as the center of their research. Iqbal's thought is very spectacular with his main theory about perfect humans, and it called 'khudi' or better known as ego. This theory is a form of criticism of fatalistic thinking and sufism pantheism, then it becomes a way to 'insan kamil'. Meanwhile, Ki Ageng Suryomentaram has the kramadangsa theory as a path to a high level of soul or known as ‘menungsa tanpa tenger'. This research aims to determine the concept of a perfect human in the perspective of Eastern Philosophy and Javanese Philosophy of Muhammad Iqbal and Ki Ageng Suryomentaram. This research is a library research using a qualitative descriptive approach. This research specifically getting more attention to the concept of soul/taste (Suryontaram), personal/ego (Muhammad Iqbal) in humans and describes all the potential aspects of humans to find points of similarities and differences in the thoughts of two figures. The result of this study is these two figures make the khudi/soul – Iqbal mentions as Ego – as the center of his attention or the material object in his research, the two figures also explain how to reach a high level in human life, the ideas of Muhammad Iqbal and Ki Ageng Suryomentaram can assess and counter the western style of Indonesia's younger generation.